Haematopoietic Stem Cell Transplantation in Adolescents and Young Adults With Acute Lymphoblastic Leukaemia: Special Considerations and Challenges - Calvo, Charlotte; Ronceray, Leila; Dhédin, Nathalie; Buechner, Jochen; Troeger, Anja; Dalle, Jean-Hugues (Frontiers in Pediatrics, 2022)
Adolescents and young adults (AYAs) represent a challenging group of acute lymphoblastic leukaemia (ALL) patients with specific needs. While there is growing evidence from comparative studies that this age group profits from intensified paediatric-based chemotherapy, the impact and optimal implementation of haematopoietic stem cell transplantation (HSCT) in the overall treatment strategy is less clear. Over recent years, improved survival rates after myeloablative allogeneic HSCT for ALL have been reported similarly for AYAs and children despite differences in transplantation practice. Still, AYAs appear to have inferior outcomes and an increased risk of treatment-related morbidity and mortality in comparison with children. To further improve HSCT outcomes and reduce toxicities in AYAs, accurate stratification and evaluation of additional or alternative targeted treatment options are crucial, based on specific molecular and immunological characterization of ALL and minimal residual disease (MRD) assessment during therapy. Age-specific factors such as increased acute toxicities and poorer adherence to treatment as well as late sequelae might influence treatment decisions. In addition, educational, social, work, emotional and sexual aspects during this very crucial period of life need to be considered. In this review, we summarize the key findings of recent studies on treatment approach and outcomes in this vulnerable patient group after HSCT, turning our attention to the different approaches applied in paediatric and adult centres. We focus on the specific needs of AYAs with ALL regarding social aspects and supportive care to handle complications as well as fertility issues. Finally, we comment on potential areas of future research and concisely debate the capacity of currently available immunotherapies to reduce toxicity and further improve survival in this challenging patient group.